If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying J + (-3) = 4 J + -3 = 4 Reorder the terms: -3 + J = 4 Solving -3 + J = 4 Solving for variable 'J'. Move all terms containing J to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + J = 4 + 3 Combine like terms: -3 + 3 = 0 0 + J = 4 + 3 J = 4 + 3 Combine like terms: 4 + 3 = 7 J = 7 Simplifying J = 7
| 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 | | 2(1[3u-7]1)=16 | | 2,5x-21=14 | | -4.6y=9.2 | | (8x^4-42x^2-10x)-3=0 | | 1-7(-2-8a)=-433 | | (-2)+(-3)+(-2)= | | 0,5x-3=15 | | -2x+1=-18 |